Aetiology, Clinical Profiles, Laboratory Profile, Outcome and Prognostic Factors of Pediatric Acute Liver Failure: Experience at a Tertiary Hospital of Bangladesh (Anwer Khan Modern Medical College Journal, 2019)
Introduction: Acute liver failure is one of the common causes of death in pediatric gastroenterology and hepatology department. Outcome is different according to aetiology.Objective: To observe the aetiology, outcome and prognostic factors of pediatric acute liver failure.Methods: Consecutive 62 children aged 2 to 16 years of age who were diagnosed as acute liver failure from November 2015 to April 2018 were included in this study. All the clinical profiles, laboratory data and outcome were recorded in a preformed data sheet. Data were analysed by SPSS for Windows version 20.Results: Mean age was 8.5 years. Thirty-nine (62.9%) patients were between 5-10 years of age. Male were 53%. We made a diagnosis of 39 (63%) patients as Wilson disease alone, Another 3 Wilson disease acute liver failure patients had concomitent with either HAV, HEV or HSV in each one. HAV only was responsible for 17 patients and HEV for 1. One patient was Haemophagocyic lymphohistiocytosis and aetiology could not be identified in 1 patient. The overall death in study population was 48% (30). Twenty-four (57%) of 42 acute liver failure patients due to Wilson disease had died. Five (29%) of 17 patients due to HAV infection and 1 patient with HLH died. Ascites, high total bilirubin, high INR and etiology like Wilson disease were the worse pronostic factors for outcome of acute liver failure in children.Conclusion: Wilson disease was the most common aetiology of acute liver failure in children in this study. Early diagnosis is essential as outcome was worse. Majority of viral etiology improved with supportive care.Anwer Khan Modern Medical College Journal Vol. 10, No. 1: Jan 2019, P 56-61